2000
DOI: 10.1002/(sici)1521-3935(20000301)201:5<479::aid-macp479>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of melt poly(ɛ-caprolactone) from inverse rheological calculation

Abstract: IntroductionThe correlation of the flow curves of a melt polymer and its molecular weight distribution (MWD) has long been a subject of discussion. The first papers on the inverse problem were published by Tuminello 1) and Malkin et al. 2)Within the last ten years, the resolution of the inverse problem has been extensively treated because the forward problem of the calculation of the dynamic moduli has received interesting new developments from a molecular point of view. For example, the concept of double rept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…This value is in agreement with M c mentioned in the literature for other aliphatic polyesters such as poly(lactic acid) (PLA) or poly( ε ‐caprolactone) (PCL). Indeed, M c of PLA has been estimated between 9000 and 16,000 g mol −1 , while that of PCL has been estimated between 8000 and 16,000 g mol −1 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is in agreement with M c mentioned in the literature for other aliphatic polyesters such as poly(lactic acid) (PLA) or poly( ε ‐caprolactone) (PCL). Indeed, M c of PLA has been estimated between 9000 and 16,000 g mol −1 , while that of PCL has been estimated between 8000 and 16,000 g mol −1 …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, M c of PLA has been estimated between 9000 and 16,000 g mol 21 , 27,28 while that of PCL has been estimated between 8000 and 16,000 g mol 21 . [29][30][31] The Activation Energy E a of Melt PBS. The activation energy E a of melt PBS was calculated from temperature-dependent shift factor a T , determined from the TTS principle.…”
Section: Articlementioning
confidence: 99%
“…There are only a few literature reports regarding the facile ROP of cyclic esters using titanium alkoxide complex initiated at ambient temperature. What is more, almost all publications reported typically by Kricheldorf et al,46 Michel et al41, 47 thought that Ti‐alkoxide bonds included in the polymer chains are extremely sensitive to water and alcohols, however, without detailed supporting data on the TiO bond stability in polymer chains. The star‐shaped structure is thought to breaks down when the resulting polymers are precipitated into methanol or exposed to moisture air 46, 47.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, almost all publications reported typically by Kricheldorf et al,46 Michel et al41, 47 thought that Ti‐alkoxide bonds included in the polymer chains are extremely sensitive to water and alcohols, however, without detailed supporting data on the TiO bond stability in polymer chains. The star‐shaped structure is thought to breaks down when the resulting polymers are precipitated into methanol or exposed to moisture air 46, 47. Recently, we have reported a preliminary result regarding the ROP of CL using tetrabutyl titanate and demonstrated that it exhibited much higher catalytic activity for ROP of CL 48.…”
Section: Introductionmentioning
confidence: 99%
“…9B shows the resulting viscoelastic master curve of the sample so in situ polymerized. From these complex moduli curves, the molecular weight distribution (MWD) of the polymer can be calculated by inverse rheological method [219] in order to investigate the structure of the poly(e-caprolactone) at the end of the polymerization process.…”
Section: Methodsmentioning
confidence: 99%